Responsibilities of Elementary School Principals in Turkey: Perceptions and Expectations - Erdogan, Cetin (KAMLA-RAJ ENTERPRISES, 2015)
The main objective of this research is to determine the expectations and perceptions of teachers and principals at public elementary schools of the responsibilities of school principals. The research was conducted in a qualitative design, and data was collected by the interview method: The participants in the study comprised 9 principals and 10 teachers from public elementary schools in 11 sub-provinces of Istanbul. A semi-structured interview form developed by the researcher was used as a data collection tool. Data was analyzed using the content analysis technique. According to the research findings, the participants perceive the concept of responsibility in school administration in the context of conscientious responsibility, parental responsibility, representation responsibility, and especially legal responsibility. School principals are, to a large extent, unable to fulfill the responsibilities expected of them, and give higher priority to finding funding sources for the school, conducting daily operations, and ensuring non-violation of legislation and school security, rather than accomplishing educational goals.
Keywords: School Administration; Administrative Responsibility; Primary Schools; Teachers; Administrative Problems; Accountability; LEADERSHIP; EXPERIENCE; STUDENTS; Anthropology; Science & Technology - Other Topics; Social Sciences - Other Topics